An exploration on integrated spatial issues in geopolitical conflict zones to describe the conceptual framework of 'Geopolitical Brownfields' - Mohsen Shojaee Far (European Regional Science Association (ERSA), 2015)
Land and urban management techniques in geopolitical conflict zones are globally associated with significant challenges, in which the built environment and their associated lands usually suffer from lack of essential elements, including, but not limited to, ownership status, accessibilities, clear governing policies, and real estate market values. To address the challenges associated with these kind of properties ? usually abandoned ? it is not sufficient to search technical solutions within the technical competence of urban planners, architects, engineers, economists, and other similar professionals and academics. According to the origins of geopolitical conflict zones, the problem was usually based on political and social conflicts associated with the geographical location of an affected area. In this sense, techniques within the social and political sciences are major elements to be associated with spatial models of analysis, would neatly fit into regional science studies. This study suggests a conceptual framework that argues the necessity of a new land typology to conceptualise the issues associated with abandoned properties in geopolitical conflict zones. Correspondingly, this paper presents the nature and origin of the proposed conceptual framework, throughout the exploration of philosophical notions of space, power, geography, and politics. The nature of this conceptual framework, borrowed from the combination of the global understanding of ?brownfield? sites and the philosophical concept of power on space, was influenced by a Foucauldian philosophical approach, producing the notion of ?geopolitical brownfields?. This conceptual framework is a new idea that is initiated by this study, and there are several important areas where this study makes an original contribution such as the field of regional science, and in particular in strategical researches on land management issues among geopolitical conflict zones. The term ?geopolitical brownfield? suggests spaces of contested powers, as all space is power and power produces space. This paper?s main concern is to advance the theoretical basis regarding challenges in dealing with disputed lands and properties in geopolitical conflict zones in a completely new conceptual framework via spatial integrated approaches, as an original methodological contribution of this study to foster the regeneration possibilities of such properties. This research tends to focus on previously vibrant urban fabrics/districts/neighbourhoods which are today abandoned/degraded as a consequence of geopolitical conflicts rather than general issues related to brownfield lands. The conceptual framework of ?geopolitical brownfields? addresses the challenges regarding abandoned properties within cities and urban settlements engulfed in domestic or international conflicts, or urban areas fractured by social and religious division. The rare case of the Cyprus conflict has had a significant impact on the nature and origin of this study, as it provided a first-hand experience of abandoned properties, frozen in time, through more than four decades of an on-going geopolitical conflict.
Keywords: 330; regional science; integrated spatial analysis; conflict zones; geopolitical brownfields; geopolitics; Cyprus